General Principles and Challenges of Public Administration Organization in Romania - Sztranyiczki, Szilárd (General Principles and Challenges of Public Administration Organization in Central Europe, 2024)
This study attempted to proceed from the foundations, exhaustively treating the topic of administrative law, and following the imposed thread of country presentations. It addressed several aspects from both theoretical and practical perspectives, primarily considering the case law of the Constitutional Court. Opinions expressed in Romanian doctrine – both post-war and post 1990 – and foreign doctrine were considered and viewpoints, suggestions and de lege ferenda proposals were expressed. Regarding Romania, it may be stated that bringing administrative law in step with the times is the merit of the doctrine as well as an intense codification activity in this field of law. Romania’s first Administrative Code was adopted in 2019, a unique legislative act in Europe where codes for administrative procedures exist. The Administrative Code establishes a comprehensive approach to Romania’s administrative territorial organization and to the organization and functioning of the authorities of local public administration, seeking to clarify the roles, powers, and competences at each administrative territorial level by complying with the principles of decentralisation, subsidiarity, and local autonomy. Citing the works of Neil Armstrong, the head of the NASA Apollo 11 mission in 1969: ‘one small step for a man, one giant leap for mankind’, the study asserts that it is perhaps a small step for the beginning, however a giant leap towards a more qualitative form of public administration in Romania.KEYWORDS Administrative Code, constitutional order, public administration, general principles, administrative territorial unit, administrative reformBibliographyAlexandru, I., Negoiţă, A., Santai, I., Brezoianu, D., Vida, I., Ivan, S., Popescu Slăniceanu, I. (1999) Drept administrative. Braşov: Editura Omnia Uni S.A.S.T.Antonescu, D. (2003) Dezvoltarea regională în România, concept, mecanisme, instituții. Editura București: Oscar Print.Antonescu, D. (2003) Romanian regional development policy in context of European Union structure. București:Institutul de Economie Națională [Online]. Available at: https://mpra.ub.uni-muenchen.de/57728/1/MPRA_paper_57114.pdf (Accessed: 12 September 2024).Apostol Tofan, D. (1997) ‘Interpretarea unor dispoziţii constituţionale privind guvernul şi administraţia ministerială’, Revista de drept public, 1–2, p. 39.Apostol Tofan, D. (2003) Drept administrativ. Tematica prelegerilor. Repere bibliografice, vol.I., (col. Curs universitar). Bucureşti: Edit. All Beck.Apostol Tofan, D. (2006) Drept administrativ, vol. I. București: Editura All Beck.Apostol Tofan, D. (2020) Drept administrativ. Volumul I. Partea introductivă. Administrația publică. Personalul din administrație. București: Editura C. H. Beck.Apostol Tofan, D. (2020) Drept administrativ. Volumul II. Actul administrativ. Contenciosul administrativ. Domeniul public. Răspunderea administrative. București: Editura C. H. Beck.Auby, J.M., Auby, J.B. (1996) Institutions administratives. 7th edn. Paris: Dalloz.Auby, J.M., Ducos-Ader, R. (1971) Institutions administratives, deuxiéme edition. Paris: Dalloz.Băhnăreanu, C., Sarcinschi, A. (2012) Procesul de regionalizare a României și securitatea națională. București: Editura Universității de Apărare ‘Carol I’ [Online]. Available at : https://cssas.unap.ro/ro/pdf_studii/procesul_de_regionalizare_a_romaniei_si_securitatea_nationala.pdf (Accessed: 12 September 2024). Bălan, E. (2002) Drept administrativ şi procedură administrativă. Bucureşti: Editura Universitară. Becet, J.-M. (1992) Les institutions administratives. Paris: Economica. Bertrand, M.J. (1973) ‘Pour une géographie du pouvoir exécutif’, Revue Internationale des Sciences Administratives, 39(4), pp. 369–382 [Online]. Available at: https://doi.org/10.1177/002085237303900405 (Accessed: 13 September 2024).Bogasiu, G. (2022) Legea contenciosului administrativ comentată și adnotată. Ediția a V-a, revăzută și adăugită. București: Editura Universul Juridic. Constantinescu, M., Iorgovan, A., Muraru, I., Vida, I., Deleanu, I., Vasilescu, F. (1992) Constituţia României comentată şi adnotată. Bucureşti: Regia Autonomă Monitorul Oficial. Delcamp, A., Loughlin, J. (eds.) (2003) La décentralisation dans les États de l’Union européenne. Paris: La Documentation Française. Deleanu, I. (2006) Instituţii şi proceduri constituţionale. Bucureşti: Editura C.H.Beck.General Principles and Challenges of Public Administration Organization in Romania Drăganu, T. (1993) Drept constituțional și instituții politice, vol.I. Târgu-Mureș: C.H. Beck. Dragoş, D.C. (2001) ‘Principalele noutăţi ale Legii nr.215/2001 a administraţiei publice locale’, Dreptul, 12(3), pp.3–31. Institutul Naţional de Statistică (2022) ‘Primele date provizorii pentru Recensământul Populației și Locuințelor, runda 2021’, Institutul Naţional de Statistică [Online]. Available at: https://www.recensamantromania.ro/wp-content/uploads/2022/12/Date-provizorii-RPL_cu-anexe_30122022.pdf (Accessed: 3 February 2023). Iorgovan, A. (2004) Noua lege a contenciosului administrativ – geneză şi explicaţii.Bucureşti: Roata. Iorgovan, A. (2005) Tratat de drept administrativ. Bucureşti: Editura All Beck. Manda, C. (2001) Drept administrativ. Tratat elementar. Bucureşti: Editura Lumina Lex. Mata, D.C. (2022) Drept administrativ. Volumul I. Ediția a IV-a. București: Editura Universul Juridic. Perioada 2021–2027 (2023) Ministerul Investițiilor și Proiectelor Europene [Online]. Available at: https://mfe.gov.ro/minister/perioade-de-programare/perioada-2021-2027/ (Accessed: 3 February 2023). Petrescu, R.N. (1997) Drept administrativ I&II. Cluj-Napoca: Editura Cordial Lex. Petrescu, R.N. (2001) Drept administrativ, ediţie revăzută şi adăugită. Cluj-Napoca: Editura Cordial Lex. Petrescu, R.N. (2004) Drept administrative. Cluj-Napoca: Accent. Petrescu, R.N. (2009) Drept administrativ. București: Hamangiu. Podaru, O., Pop, M.M. (2020) ‘Provocările limbajului în Codul administrativ’, Studia Universitatis Babeș-Bolyai. Iurisprudentia, 65(1), pp. 30–68 [Online]. Available at: https://doi.org/10.24193/SUBBiur.65(2020).1.3 (Accessed: 6 Feburary 2023). Popescu, C.L. (1999) Autonomia locală şi integrarea europeană. Bucureşti: Editura All Beck. Preda, M.,Vasilescu, B. (2007) Drept administrativ. Partea specială. Bucureşti: Lumina Lex. Prisăcaru, V.I. (2002) Tratat de drept administrativ român. Partea generală. București: Lumina Lex. Puie, O. (2022) Tratat teoretic și practic de contencios administrativ, vol 1,2 si 3, ediția a II-a revizuită. București: Editura Universul Juridic. Săgeată, D.R. (2004) Modele de regionare politico-administrativă. București: Top Form. Săgeată, D.R. (2006) Deciziile politico-administrative şi organizarea teritoriului: studiu geografic cu aplicare la teritoriul României. București: Top Form. Săgeată, D.R. (2011) ‘Reformele administrative din România- între rațiunile politice și realitățile geografice’, Geograf ul, 3(1-2) [Online]. Available at: https://www.academia.edu/download/38849970/Reforma_administrativa_in_Romania.pdf (Accessed: 13 September 2024). Săraru, C.S. (2022) Tratat de contencios administrativ. București: Editura Universul Juridic. Schwarze, J. (1994) Droit admistratif europeen. Bruxelles: Bruylant. Schwarze, J. (1996) Le droit administratif sous l’ influence de l’ Europe. Une étude sur la convergence des ordres juridiques nationaux dans l’ Union européenne. Bruxelles: Bruylant. Se schimbă legea organizării administrativ-teritoriale a României (2016) Economica.net, 17 October [Online]. Available at: http://www.economica.net/se-schimba-legea-organizarii-administrativ-teritoriale-a-romaniei_127063.html#ixzz4sgGPlNFT (Accessed: 3 February 2023). Ștefan, E.E. (2022) Curs de drept administrativ. Manual de drept administrativ. Partea II. București: Editura Universul Juridic. United Nations (2023) ‘Transforming our world: the 2030 Agenda for Sustainable Development’ [Online]. Available at: https://sdgs.un.org/2030agenda (Accessed: 3 Februar y 2023). Van Lang, A., Gondouin, G., Inserguet-Brisset, V. (1999) Dictionnaire de droit administratif. Paris: Armand Collin.Vedinaș, V. (2022) Drept administrativ. Ediția a XIII-a, revăzută și actualizată, Doctrină, practică și jurisprudență. București: Universul Juridic. Vedinaș, V. (2023) Codul administrativ comentat. Explicații, jurisprudență, doctrină. volumul I și volumul II. București: Universul Juridic. Vida, I. (1994) Puterea executivă şi administraţia publică. Bucureşti: Editura Universul Juridic. Vrabie, G., Bălan, M.M. (2004) Organizarea politico-etatică a României. Iaşi: Institutul European. Zăman, G.H. (2015) Experienţa tranziţiei României la economia de piaţă (1990–2014).